2023
DOI: 10.3390/en16207049
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Energy Development: History and Recent Advances

Joseph Akpan,
Oludolapo Olanrewaju

Abstract: Sustainable energy development (SED) is a crucial component of the Sustainable Development Goals (SDG), aiming to maintain economic and social progress while protecting the environment and mitigating climate change’s effects. SED serves as a transition paradigm for sustainable development, providing a blueprint for energy peace and prosperity for people and all uses. This article presents the history of SED and then uses a critical discourse approach to summarize existing review studies in SED. Ten interlinked… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…Analyzing the dynamics of changes in the values of synthetic measures in individual countries, it can be observed that the vast majority of EU countries have not achieved lasting sustainable energy development. Using the 2014 value as the base value, it can be noted that in most countries (15) in the following years (2015-2021) these measures were at a lower level than in 2014. This means that in these countries, in the subsequent years 2015-2021, compared to 2014, there were no positive changes in the area of sustainable energy.…”
Section: Research Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Analyzing the dynamics of changes in the values of synthetic measures in individual countries, it can be observed that the vast majority of EU countries have not achieved lasting sustainable energy development. Using the 2014 value as the base value, it can be noted that in most countries (15) in the following years (2015-2021) these measures were at a lower level than in 2014. This means that in these countries, in the subsequent years 2015-2021, compared to 2014, there were no positive changes in the area of sustainable energy.…”
Section: Research Resultsmentioning
confidence: 99%
“…Despite the relative popularity of this topic, there is currently no research that would analyze these two key areas of sustainable development jointly. There are many studies that examine either sustainable energy development [9,15,17,18,[80][81][82][83] or sustainable economic development [84][85][86][87][88][89][90][91][92], but none that presents research results regarding both, plus their mutual relationship. Only in selected European Commission documents can one find statements and conclusions indicating that, for example, a long-term interruption in energy supply would have a significant impact on the EU economy [93][94][95].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In response to the pressing need for transitioning towards cleaner and more sustainable energy systems, higher education institutions took significant steps to broaden their energy studies programs. These expansions included incorporating coursework and research focused on renewable energy technologies, energy efficiency measures, and environmental sustainability practices [28].…”
Section: The Evolution Of Education Systems In Context Of Energymentioning
confidence: 99%
“…Table 3. The fundamental scale [28] for pairwise comparisons (l -lower fuzzy number, m -middle fuzzy number, u -upper fuzzy number).…”
Section: 𝐹 = 𝑚𝑖𝑛{𝑙} (∏ {𝑚}) Max {𝑢}mentioning
confidence: 99%